The Use of Virus-like Particles as Immunogens to Treat Infectious Diseases. - da Silva Sanches, Paulo Ricardo [UNESP]; Cilli, Eduardo Maffud [UNESP] (Bentham Science Publishers, 2025)
Virus-like particles (VLPs) represent a promising approach to developing vaccines for infectious diseases. These nanostructures mimic the organization and conformation of native viruses but lack viral genetic material, rendering them non-infectious. VLPs can induce potent immune responses, making them ideal immunogens. This review provides an overview of VLP technology, its application in combating infectious diseases, and its potential to shape future vaccine development. Specific emphasis is placed on current clinical applications, emerging infectious disease targets, and the challenges in optimizing VLP-based immunogens.